Psychologic Stress of COVID-19 Pandemic and Oral Health: A Case Series - Fu, Wendy; Shah, Raime; Curtis, Donald A; Kapila, Yvonne (Archives of Clinical and Medical Case Reports, 2021)
Introduction: High stress levels associated with the COVID-19 pandemic may be a risk factor for accelerating inflammatory disease processes, such as periodontitis and peri-implant disease, and parafunctional activities, such as bruxism. Case Presentation: The purpose of this report is to outline unique clinical examples of complications observed in our clinics during the COVID-19 pandemic, review potential mechanisms of action, and offer general recommendations. Conclusions: The consideration of how high levels of psychologic stress might impact patient management is relevant.